Neutralization as a Strategy to Translate the Affectiveness of Microtales [la Neutralización Cultural Como Estrategia Para la Traducción de la Afectividad de Microcuentos] - Singer-Contreras, N (Universidade Federal de Santa Catarina, 2019)
This article aims to translate the emotional factor in 16 short stories of Santiago en 100 Palabras by exploring new strategies to produce a semantic-affective translation. Specifically, this research highlights neutralization (Aixela) as a means to achieve an emotional equivalence in such text typologies. Data collection was carried out by the implementation of a survey to collect the emotions produced in 32 Spanish speakers and 20 English speakers. From this information, a three-step methodology was performed: i) translation proposal, ii) validation, and iii) final editing. The results indicate emotional equivalence was achieved in 81% of the short stories. As to those cases of emotional incongruence, it is considered it may be due to three possible reasons: i) textual typology conventions, and ii) emotional subjectivity. In conclusion, cultural neutralization is considered an appropriate strategy to achieve emotional equivalence between these two languages in the selected corpus. © Universidade Federal de Santa Catarina.